Procurement, traceability and advance cash credit payment transactions in supply chain using blockchain smart contracts. (May 2022) - Raj, Praveen Vijaya Raj Pushpa; Jauhar, Sunil Kumar; Ramkumar, M.; Pratap, Saurabh
Highlights: We proposed a smart contract-based conceptual framework. Framework allows all stakeholders to participate, access information and build trust. Ensures the protection of payments without administrative costs and the burden. Provides accurate product tracking to eliminate many complications in supply chain. Proposed smart contract framework is validated and tested in a variety of scenarios. Abstract: Timely payment is necessary for the efficient delivery of goods and services to all entities in the supply chain. Traditionally, there has been a lot of manual processes related to payment. Nowadays the technology advancements make the payment process in electronic form. Even the electronic form is not easily accessible to all parties in the supply chain. Each entity of the supply chain maintains separate transaction records that remain difficult, inefficient, and error prone. Often companies face difficulties in monitoring the status of shipments and linking them to payments. In the real world, the suppliers offer buyers three terms of payment of purchase costs. The buyer pays the supplier as advance payment, cash, or credit. This research considers that the supplier ships the goods to the buyer by means of third-party logistics services. The supplier initially pays an advance to the external logistics provider while shipping the product to the buyer. Once the buyer verify that the goods are received in correct quantity, the supplier shall pay the balance amount to the third-party logistics provider. This research proposes a blockchain-based smart contract for supply chain transactions. This paper presents a general platform for stakeholders in the supply chain through an Ethereum based smart contract with comprehensive interaction algorithm that enables decentralized authorization, process automation, and information sharing between the supply chain stakeholders. The proposed smart contract benefits the supplier by lowering the risk of non-payment during the credit period. In addition, the buyer benefits from on-time delivery performance and product tracking. Finally, the 3PL significantly reduces their costs by lowering the overall cost by lowering the cost of paperwork and usage of software for product tracking. Adopting a blockchain-based solution in supply chain transaction considering ACC payment is cost-effective simple, secure, trustworthy, and transparent.